A production and operations management study on G.E. Lighting Philippines - Montañez, Mario V. III; Rosario, Michael B.; Torres, Gwen P. (Diliman, Quezon City College of Engineering, 1999)
General Electric (GE) Lighting Philippines is the manufacturer of GE brand incandescent and fluorescent lamps of different types and wattage. It has recently been ISO 9002 certified last November 30, 1998. The study team documented the different within the plant operations involved in the production of the 40W fluorescent lamp and analyzed the system and found ways to improve the operations in the plant. One of the major problems discussed in the paper is the inaccurate forecast fort the past three years made by the marketing department of GE Lighting. The study team then suggested the use of the exponential smoothing forecasting technique to predict the demand for the product under study. In addition, with the closure of its biggest competitor during the last quarter of 1998, the market share of GE increased by more than 20 percent. This posed a problem regarding the capacity of the plant if the company would be able to meet the forecasted demand. The study team recommended the replacement of the existing machine with a new machine with higher capacity. This would enable the company to meet the forecasted demand with minimal additional cost in the long run. The last problem tackled by the study team was the late arrival of raw materials due to the unreliability of the suppliers. The team then suggested some modifications in the Supplier Evaluation Form to be able to rate the suppliers according the criteria that are in relation with the company's objectives.
Feasibility study